Cole parameters of human blood with different anticoagulants - Şimşek, Fatma Gülden. (Thesis (M.S.) - Bogazici University.Institute of Biomedical Engineering, 2011., 2011)
Impedance spectroscopy of blood samples with Acid Citrate Dextrose, Ethylene Diamine Tetra-acetic Acid, Lithium Heparin and Sodium Citrate anticagulants are performed in the frequency range 20 Hz-1MHz, using the two probe method, at room temperature. The measurement cell is a cylindrical-like plastic tube of 1.45 cm diameter and 14 ml volume with two stainless-steel electrodes. Blood samples of 5 ml are drawn from 9 healthy male donors between ages 22 to 28, and centrifuged at 5500 rpm for 8 minutes to constitute different hematocrit values in the range from 29 % to 60 %. Multifrequency impedance measurement are fitted to Cole-Cole diagrams using the Matlab algorithm; Cole parameters R0, R, fc and alfa are then used to model the equivalent electrical circuit of blood. Only high frequency data (100kHz-1MHz) are used in fitting the Cole circle where effects of electrode polarization are negligible. It is later shown that this is acceptable since the characteristic frequency of the blood samples occurs around few MHZ. Resistivities of plasma alone are measured as 70 .... for EDTA, LH, SC and ACD respectively. At 100 % hematocrit when extracellular conductivity is zero the intracellular resistivities are 200 cm. for EDTA; 214 cm for LH; 261 cm for SC and 176 cm for ACD. The rate of increase in extracellular resistance with Ht is measured higher with LH and EDTA. In the physiological range of hematocrits, Re is the highest with LH and lowest with SC; at h=0.6 LH samples are 34 % higher than SC samples. The characteristic frequency fc changes with the type of anticoagulant ; the frequency span at Ht=50 % is from 0.8 MHz (LH) to 1.1 MHz (ACD). The angle of depression is the highest with LH.|Keywords : Erythrocyte, hematocrit, electrical impedance of blood, impedance spectroscopy, Cole-Cole plot, Maxwell-Fricke Formula.
Keywords: Blood pressure.; Erythrocytes.; Hematocrit.; Impedance spectroscopy.